Ethical Leadership and Knowledge Sharing: The Impacts of Prosocial Motivation and Two Facets of Conscientiousness - Xia, Zhichen; Yang, Fan (Frontiers in Psychology, 2020)
This study adopts the social learning theory to explain how and when ethical leadership can predict knowledge sharing in the context of Chinese higher education. We collected two-wave data from 302 postgraduate students from 38 scientific research teams in Chinese universities. The results of this study show that ethical leadership has a direct and positive effect on knowledge sharing, and prosocial motivation fully mediates this relationship. Moreover, the boundary conditions for such effects have affirmed the positive effects of dutifulness and the adverse effects of achievement-striving on the relationship between prosocial motivation and knowledge sharing. The indirect effects of ethical leadership on knowledge sharing are stronger when dutifulness is high and achievement-striving is low. Several theoretical and practical implications are provided by this study. It suggests that the role of prosocial motivation, in tandem with the two facets of conscientiousness, deserves to be highlighted when studying knowledge sharing behaviour in correlation with ethical leadership.